CRS SEISMIC PROCESSING OF A GEOLOGICAL COMPLEX AREA - Jiménez, Eduardo; Vargas, Carlos A.; Montes, Luis A. (Earth Sciences Research Journal, 2009)
We applied the NMO and CRS (Common Reflector Surface) approaches to a complex geological area in order to compare their performances for obtaining enhanced images. Unlike NMO, CRS does not depend on a previous time velocity model and uses a hyperbolic equation to estimate 2D travel times through three parameters (Normal ray emergence angle, NIP and N wavefront curvatures). To obtain the image a solution provided by coherence analysis algorithm was used. A low quality Colombian seismic line acquired in Middle Magdalena basin was used, where a foothill geological area is characterizedby a thrusting fault. The CRS provided an enhanced image which allowed a new geological interpretation that is best constrained with other regional observations.